The Effect Of Intellectual Capital And Sustainbility Report Disclosure On Company Value With Profitability As A Moderation Variable: (Empirical Studies in Manufacturing Companies 2017-2021) - Intan Saputri Ayuningtiyas; Fidiana; Titik Mildawati (Lead Journal of Economy and Administration, 2023)
This study aimed to examine the effect of intellectual capital (VAICTM) and sustainability report disclosure (GRI-G4) on firm value (Tobin’s Q), with profitability (ROA) as the moderating variable. The study was quantitative. Moreover, the population was manufacturing companies listed on the Indonesia Stock Exchange for 5 years (2017-2021). The data collection technique used purposive sampling. In line with that, there were 25 companies as the sample. In total, 125 data samples were obtained. Furthermore, the data analysis technique used multiple linear regression and interaction test of Moderated Regression Analysis (MRA), with SPSS 21. As the result, it concluded that intellectual capital (VAICTM) had a positive effect on firm value. It meant, companies with strong intellectual capital could develop effective strategies in order to manage the sources, by adding some business values. Sustainability Report Disclosure (GRI- G4) had a positive effect on firm value. This meant since companies were aware of presenting activities, in the economy, environment, and society; the decision makers would have the information that they needed in increasing reputation capital from the companies. As a consequence, the firm value increased. Profitability (ROA) could not moderate the effect of intellectual capital on firm value. In other words, when companies had losses in a certain period, they would have efficiency in order to minimize the cost. Additionally, profitability (ROA) could not moderate the effect of sustainability report disclosure (GRI-G4) on firm value. It happened as profitability could not become the main support of companies’ policy in having social activities and making sustainability reports since companies were not always profitable.